Developing a current capability design for a manufacture framework in the aerospace industry - Whiteside, A. (Cranfield University, 2008)
During progressive product design and development in the aerospace industry, a lack of effective communication between the sequential functions of design, manufacturing and assembly causes delays and setbacks whereby production capabilities are unable to realise design intent in high-complexity product models. There is a need to formalise the progressive design and release of an engineering model to production functions during New Product Introduction (NPI) via defining key stages of definition maturity and information requirements through a structured process. This research develops a framework to facilitate optimal Design for Manufacture and Assembly (DfMA) based on current manufacturing capabilities within the aerospace industry, promoting effective knowledge management at all stages of design definition. The framework was developed through the accomplishment of a series of objectives: (1) Investigate optimal DfMA principles and process capability analysis through a comprehensive literature review, (2) capture the current practice of progressive drawing release in the aerospace and automotive sectors, (3) create a route map of the release process built around the optimal critical path, (4) define roles and procedures to follow at each stage and (5) validate the proposed process framework through expert opinion. These objectives were achieved through the adoption of a four-stage qualitative methodology. The framework promotes the understanding and identification of the major stages, activities, responsibilities and information requirements throughout a structured design release process where quantified manufacturing capability data is incorporated within early design definition activities. Adherence to the process route-map ensures that no engineering model is released that cannot be realised by manufacturing and assembly functions. This facilitates the efficient organisation of information on an optimal concurrent engineering platform, leading to a reduction in product development leadtimes and re-work through informed design.
Keywords: Design for Manufacture and Assembly; Process Capability Analysis